Does the timing of implant placement and loading influence biological outcomes of implant‐supported multiple‐unit fixed dental prosthesis—A systematic review with meta‐analyses. (12th October 2021) - Aiquel, Louise Leite; Pitta, João; Antonoglou, Georgios N.; Mischak, Irene; Sailer, Irena; Payer, Michael
Abstract: Objective: To investigate the impact of timing of implant placement and loading on implant survival and biological outcomes of multiple‐unit implant‐supported fixed dental prosthesis (FDPs). Material and Methods: A literature search was performed by three independent reviewers for studies reporting on ≥10 patients with FPDs supported by ≥two implants over ≥3 years of follow‐up. Data were analyzed on implant survival and biological complications as primary outcomes and biological events, including changes in peri‐implant marginal bone level (MBL), probing depth, soft‐tissue level, and health condition as secondary outcomes. Results: 7002 titles were identified, 360 full‐texts were screened, and 14 studies were included. These comprised 6 randomized controlled studies (RCTs), 5 cohort studies, and 3 case series with identifiable implant placement and loading protocols in five of 09 possible combinations. All groups but one (IPIL) showed implant survival rates >90%. A meta‐analysis based on 3 RCTs found no differences in survival rate between DPIL and DPDL ( p  = .227). Conclusions: High survival rates for all studied implant placement and loading combinations were shown for FPDs over ≥3 years of follow‐up. When a delayed implant placement protocol is applied, immediate or delayed loading demonstrated similar survival rates. The heterogeneity of the data did not allow to draw any further conclusions on the occurrence of biological complications related to timing of implant placement/loading.